The Src-Kinase Fyn is Required for Cocaine-Associated Memory Through Regulation of Tau - Li, Hongchun; Zhou, Xinglong; Chen, Rong; Xiao, Yuzhou; Zhou, Tao (Frontiers in Pharmacology, 2022)
Drug-associated context-induced relapse of cocaine-seeking behaviour requires the retrieval of drug-associated memory. Studies exploring the underlying neurobiological mechanism of drug memory formation will likely contribute to the development of treatments for drug addiction and the prevention of relapse. In our study, we applied a cocaine-conditioned place preference (CPP) paradigm and a self-administration paradigm (two drug-associated memory formation model) to confirm the hypothesis that the Src kinase Fyn critically regulates cocaine-associated memory formation in the hippocampus. For this experiment, we administered the Src kinase inhibitor PP2 into the bilateral hippocampus before cocaine-CPP and self-administration training, and the results showed that pharmacological manipulation of the Src kinase Fyn activity significantly attenuated the response to cocaine-paired cues in the cocaine-CPP and self-administration paradigms, indicating that hippocampal Fyn activity contributes to cocaine-associated memory formation. In addition, the regulation of cocaine-associated memory formation by Fyn depends on Tau expression, as restoring Tau to normal levels disrupted cocaine memory formation. Together, these results indicate that hippocampal Fyn activity plays a key role in the formation of cocaine-associated memory, which underlies cocaine-associated contextual stimulus-mediated regulation of cocaine-seeking behaviour, suggesting that Fyn represents a promising therapeutic target for weakening cocaine-related memory and treating cocaine addiction.